2011
DOI: 10.5194/acpd-11-12251-2011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Large Asian dust layers continuously reached North America in April 2010

Abstract: The NASA space-borne Mie-lidar system CALIPSO/CALIOP revealed that multiple large Asian dust layers with a horizontal scale of 2000–3000 km reached North America, occupying the full troposphere, in April 2010. This kind of dust layer transport has not been reported before. Our analysis of CALIOP data and global aerosol model results revealed that frequent dust emissions occurred in northwestern China because of stronger-than-average near-surface winds, and that strong stable westerly winds carried the Asian du… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
27
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(28 citation statements)
references
References 15 publications
1
27
0
Order By: Relevance
“…Though Asian dust primarily affects the western U.S. and Canada due to closer proximity and difficulties in transport over the mountains (Fairlie et al, 2007;Zhao et al, 2008), sufficiently strong high-level western jets can push the lofted plumes to the eastern U.S. For instance, an event of Asian dust transport to the mid-Atlantic U.S. was observed during Apr.17e20, 2006 (Delgado et al, 2011). Uno et al (2011) show a few Asian dust transports to the eastern U.S. with a global aerosol transport model and CALIPSO data in spring 2010; and Cottle et al (2013) also demonstrate these pervasive Asian dust events in both western and eastern Canada but in this case, avoiding the most treacherous mountain obstructions. To our best knowledge, in contrast to the extensive analysis of Asian dust impacts in the western U.S. and Canada, quantitative demonstrations are not well documented in the eastern U.S.…”
Section: Introductionmentioning
confidence: 94%
See 1 more Smart Citation
“…Though Asian dust primarily affects the western U.S. and Canada due to closer proximity and difficulties in transport over the mountains (Fairlie et al, 2007;Zhao et al, 2008), sufficiently strong high-level western jets can push the lofted plumes to the eastern U.S. For instance, an event of Asian dust transport to the mid-Atlantic U.S. was observed during Apr.17e20, 2006 (Delgado et al, 2011). Uno et al (2011) show a few Asian dust transports to the eastern U.S. with a global aerosol transport model and CALIPSO data in spring 2010; and Cottle et al (2013) also demonstrate these pervasive Asian dust events in both western and eastern Canada but in this case, avoiding the most treacherous mountain obstructions. To our best knowledge, in contrast to the extensive analysis of Asian dust impacts in the western U.S. and Canada, quantitative demonstrations are not well documented in the eastern U.S.…”
Section: Introductionmentioning
confidence: 94%
“…Asian dust storms, originating from the deserts of eastern and central Asia, often inject large amount of dust particles into atmosphere which can be transported to North America (NA) across the Pacific Ocean due to the combined effects of active extratropic cyclones and the strong mid-latitude western wind (Huebert et al, 2003;Stith et al, 2009;Uno et al, 2011). Somewhat surprisingly, even after long range transport, trans-Pacific Asian dust can pose significant impacts on the air quality and climate radiation in NA.…”
Section: Introductionmentioning
confidence: 99%
“…Whenever air masses reach the North American west coast, subsidence motion and mountain waves bring dust down to the ground (McKendry et al, 2008). This framework has been supported by dispersion modeling of trans-Pacific dust transport (Uno et al, 2011) and by observations: VanCuren and Cahill (2002) have found a distinctive spring peak of crustal aerosol reaching remote sites in western North America; Zhao et al (2008) found a correlation of 0.83 between ground level PM 10 at US sites and frequency of Asian desert storms in 2000-2006and Cottle et al (2013) have used lidar and sunphotometer network data to backtrack Asian dust plumes reaching Canada and northern USA in spring 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Huang et al, , 2014. They can travel over thousands of kilometers, even across the Pacific Ocean, and reach the western coast of North America in about 1 week with the prevailing westerly wind (Husar et al, 2001;Uno et al, 2009Uno et al, , 2011. They then modify the climate and environment over extensive areas of the Asia-Pacific rim.…”
Section: Introductionmentioning
confidence: 99%